NF-κB-Like Signaling Pathway REL2 in Immune Defenses of the Malaria Vector Anopheles gambiae - Zakovic, Suzana; Levashina, Elena A. (Frontiers in Cellular and Infection Microbiology, 2017)
The blood feeding requirements of insects are often exploited by pathogens for their transmission. This is also the case of the protozoan parasites of genus Plasmodium, the causative agents of malaria. Every year malaria claims the lives of a half million people, making its vector, the Anopheles mosquito, the deadliest animal in the world. However, mosquitoes mount powerful immune responses that efficiently limit parasite proliferation. Among the immune signaling pathways identified in the main malaria vector Anopheles gambiae, the NF-κB-like signaling cascades REL2 and REL1 are essential for eliciting proper immune reactions, but only REL2 has been implicated in the responses against the human malaria parasite Plasmodium falciparum. Instead, constitutive activation of REL1 causes massive killing of rodent malaria parasites. In this review, we summarize our present knowledge on the REL2 pathway in Anopheles mosquitoes and its role in mosquito immune responses to diverse pathogens, with a focus on Plasmodium. Mosquito-parasite interactions are crucial for malaria transmission and, therefore, represent a potential target for malaria control strategies.